Case Report: Talaromyces marneffei Infection in a Chinese Child With a Complex Heterozygous CARD9 Mutation - Ba, Hongjun; Peng, Huimin; Cheng, Liangping; Lin, Yuese; Li, Xuandi; He, Xiufang; Li, Shujuan; Wang, Huishen; Qin, Youzhen (Frontiers in Immunology, 2021)
Talaromyces marneffei (TM) infection is rarely seen in clinical practice, and its pathogenesis may be related to deficiency in antifungal immune function. Human caspase recruitment domain-containing protein 9 (CARD9) is a key molecule in fungal immune surveillance. There have been no previous case reports of TM infection in individuals with CARD9 gene mutations. Herein, we report the case of a 7-month-old Chinese boy who was admitted to our hospital with recurring cough and fever with a papular rash. A blood culture produced TM growth, which was confirmed by metagenomic next-generation sequencing. One of the patient’s sisters had died of TM septicaemia at 9 months of age. Whole exome sequencing revealed that the patient had a complex heterozygous CARD9 gene mutation with a c.1118G>C p.R373P variation in exon 8 and a c.610C>T p.R204C variation in exon 4. Based on the culture results, voriconazole antifungal therapy was administered. On the third day of antifungal administration, his temperature dropped to within normal range, the rash gradually subsided, and the enlargement of his lymph nodes, liver, and spleen improved. Two months after discharge, he returned to the hospital for a follow-up examination. His general condition was good, and no specific abnormalities were detected. Oral voriconazole treatment was continued. Unexplained TM infection in HIV-negative individuals warrants investigation for immune deficiencies.